2018
DOI: 10.3390/ijerph15061163
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Exposure of Pregnant Women and Neonates in Agricultural Areas in Thailand

Abstract: This study aimed to assess paraquat concentrations in the urine of women at 28 weeks of pregnancy, delivery and 2 months postpartum and in the meconium of neonates. In all, 79 pregnant women were recruited from three hospitals located in agricultural areas in Thailand. The subjects were interviewed about personal characteristics, agricultural activities and pesticide use patterns. Paraquat was analyzed in urine and meconium using high performance liquid chromatography equipped with a fluorescence detector. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…Apart from deliberate intake, people can also be chronically exposed to PQ owing to the pesticide residues in daily foods. In supervised trials, PQ has been detected in many farm products (Francesquett et al, ; Lei, Li, Chen, & Xu, ; Zhang et al, ), and epidemiological investigation found that PQ even exists in neonatal meconium (Konthonbut et al, ), highlighting the need to study the adverse effects of PQ on the health of the general population. Owing to the structural similarity with the neurotoxicant MPP+ and induction of oxidative stress (Cocheme & Murphy, ), the neurotoxicity of PQ on human as well as animal models has been generally accepted (Costello, Cockburn, Bronstein, Zhang, & Ritz, ; Li et al, ; Tanner et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from deliberate intake, people can also be chronically exposed to PQ owing to the pesticide residues in daily foods. In supervised trials, PQ has been detected in many farm products (Francesquett et al, ; Lei, Li, Chen, & Xu, ; Zhang et al, ), and epidemiological investigation found that PQ even exists in neonatal meconium (Konthonbut et al, ), highlighting the need to study the adverse effects of PQ on the health of the general population. Owing to the structural similarity with the neurotoxicant MPP+ and induction of oxidative stress (Cocheme & Murphy, ), the neurotoxicity of PQ on human as well as animal models has been generally accepted (Costello, Cockburn, Bronstein, Zhang, & Ritz, ; Li et al, ; Tanner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The developing brain is more vulnerable to neurotoxicant exposure than the mature one, particularly during critical windows such as in utero and early childhood (Rice & Barone, ). In fact, studies implicated that PQ can cross the placenta and reach the fetus in the rats, mice and humans (Bus et al, ; Konthonbut et al, ). Besides, PQ exposure in early life has been associated with neurodevelopmental and neurodegenerative diseases (Fredriksson, Fredriksson, & Eriksson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Selain itu, konsentrasi paraquat dalam urin juga ditemukan pada ibu yang tinggal disekitar area pertanian Thailand, yaitu pada ibu dengan kehamilan 28 minggu, ibu bersalin dan 2 bulan setelah melahirkan masing-masing adalah 2,04, 2,06 dan 2,42 ng/mL. 30 Dari beberapa penelitian tersebut konsentrasi paraquat dalam urin tidak hanya ditemukan pada pekerja yang melakukan penyemprotan paraquat, tetapi juga ditemukan pada ibu yang tinggal di sekitar area pertanian. Berdasarkan fakta yang telah diuraikan, penelitian ini bertujuan untuk menganalisis konsentrasi paraquat dalam urin pekerja akibat paparan paraquat dan faktor yang mempengaruhinya di perkebunan kelapa sawit.…”
Section: Pendahuluanunclassified
“…[14][15] In particular, lower urinary tract symptoms signi cantly affect the quality of life by causing physical, mental, and social problems rather than being life threatening, which necessitates an investigation among male farmers using hazardous substances such as pesticides many of whom are in their middle age. Other countries have conducted various studies on pesticides including cohort studies on exposure during pregnancy [16][17] or to examine the relationship with speci c diseases such as diabetes and prostate cancer 7,18. In the case of South Korea, however, studies have mostly focused on the assessment of pesticide exposure and there is no study conducted on the effect of pesticides on health.…”
Section: Introductionmentioning
confidence: 99%